(untitled) (Global Journal of Science Frontier Research, 2015)
Seed flow through hopperorifices is found in systems of dosing-filling-packaging; in hopper feeding systems; and in technological processes for control and/or monitoring.This study was aimed at establishing the relationship between moisture content and the volumetric flow rate (Q) of egusi-melon (Colocynthis citrullus)seeds as they passed through horizontal hopper orifices. It is observed that Q decreased as the moisture content increased due probably to the increase in internal friction as the moisture content increased as well as the change in bulk density with moisture. When egusi-melon moisture content increased from 6.76 to 18.9% d.b., the Q through circular and square horizontal hopper orifices decreased by about 5.36% from 3.5848 to 3.3926m 3 /h (circular) and by about 4.36% from 2.3459 to 2.2436 m 3 /h (square), showing higher Q for circular than for square orifice. Also, Q had a negative linear relationship with moisture content with R 2 = 0.91. However, for increasing hopper orifice sizes, Q increased with power regression with exponents ranging from 2.54 to 2.95 for both orifices and for equivalent orifice diameter (D e ) and hydraulic orifice diameter (D h ). This study is important for proper design of hoppers and outlet nozzles to facilitate uninterrupted egusi-melon seed flow rate.